A comparison study of the blower door and novel pulse technique on measuring enclosure airtightness in a controlled environment - Zheng, Xiaofeng; Cooper, Edward; Mazzon, Joe; Wallis, Ian; Wood, Christopher J. (2017)
This paper introduces a comparison study of measuring the airtightness of a house sized test chamber using the novel pulse technique and the standard blower door method in a controlled environment. Eight different testing plates have been applied to the improvised envelope of the chamber to establish different leakage characteristics. Each testing plate has a unique opening in the centre of the plate, achieved by obtaining a different combination of shape and thickness of the opening. By using the controlled environment, the vagaries of the natural condition when testing within buildings have been reduced providing a more robust testing environment. This investigation focuses on how the air leakage rate calculated from the measurements made by both techniques compare with each other. Comparable results (within 3 %) under most scenarios have been obtained. Additionally, other aspects such as usability of the equipment used for the pulse testing have also been appraised.